Quality parameters for the e-learning Omega system - Klasnić, Ksenija, sociologinja (Array, 2008)
Learning and teaching are considered to be the main activities in higher education. The environment in which these activities take place is rapidly changing and it is getting more and more oriented towards teaching with the help of the new technologies, namely e-learning system, relying not only on technical skills but also on motivation and contextualisation. In the paper, different views towards the quality of e-learning have been presented, and the research regarding the quality of the e-learning Omega system (Moodle) conducted at the Faculty of Humanities and Social Sciences, University of Zagreb presented in relation to different European policies.